Nitrogen Fertilizer Management for Enhancing Crop Productivity and Nitrogen Use Efficiency in a Rice-Oilseed Rape Rotation System in China - Yousaf, Muhammad; Li, Xiaokun; Zhang, Zhi; Ren, Tao; Cong, Rihuan; Ata-Ul-Karim, Syed Tahir; Fahad, Shah; Shah, Adnan N.; Lu, Jianwei (Frontiers in Plant Science, 2016)
The use of efficient rates of nitrogen (N) fertilizer application is important with regard to increasing crop productivity and maintaining environmental sustainability. Rice-oilseed rape rotations are a mainstay of the economy and food security of China. Therefore, a field experiment was carried out during 2011–2013 in Honghu to identify the most appropriate N application rates for enhancing crop productivity and N use efficiency for rice (Oryza sativa L.)-oilseed rape (Brassica napus L.) rotations. Six N fertilizer treatments (RO1, RO2, RO3, RO4, RO5, and RO6) were laid out in a randomized complete block design with three replicates. ROx represented the N fertilizer application rates (kg ha–1) for rice and oilseed rape, respectively. Grain yields from plots receiving N fertilizer were significantly increased by 59–71% (rice) and 109–160% (oilseed rape) during the total rotation (2011–2013), as compared to RO1 (control; no application). Furthermore, a similar trend was observed for N accumulation, ranging from 88–125% and 134–200% in aerial parts of rice and oilseed rape, respectively. Nitrogen use efficiency (NUE) was significantly higher (38.5%) under RO2 and lower (34.2%) under RO6 while apparent N balance (ANB) was positively lowest under R05 (183.4 kg ha–1) followed by R02 (234.2 kg ha–1) and highest under R06 (344.5 kg ha–1) during the total rotation. The results of grain yield, NUE, and ANB indicated that the R02 rate of N application was superior. This information should help to develop a cost-effective and environment-friendly N management strategy for rice-oilseed rape rotation systems of central China.